Partnerships with asymmetric information: The benefit of sharing equally amongst unequals - Nana Adrian; Marc Möller (University of Bern, Department of Economics, 2019)
This paper provides a rationale for equal sharing in heterogeneous partnerships. We introduce project choice and information sharing to a standard team production setting. A team with two agents can choose whether they want to work on a status quo project or on an alternative project. If the (expected) quality of the projects is given and common knowledge, it is optimal for team surplus to give a higher share to the more productive agent in order to optimally motivate. If agents have private information, we have to give the higher share of profits to the less productive agent if we want agents to share this information, which would allow for better adaptation. Equal revenue-sharing strikes a balance between the two objectives of adaptation and motivation and can be effcient even in the presence of considerable productivity dfferences across partners.
Keywords: D2; D8; L2; 330; Team adaptation; effort motivation; information disclosure